Pengaruh Strategi Diversifikasi Perbankan Terhadap Kinerja Bank Papua - Candra Andhika (Jurnal Akuntansi, Manajemen dan Ekonomi, 2021)
This study aims to describe the performance of Bank Papua after diversification and to analyze the effect of diversification strategies on the performance of Bank Papua. This research is a quantitative study with a population of 37 Bank Papua branch offices throughout Indonesia. The data source used is secondary data in the form of financial reports for 2016-2018. Data analysis using descriptive analysis and linear regression. The results showed that the diversification strategy carried out by Bank Papua had a significant and negative effect on the performance of Bank Papua as indicated by a significance value of 0.038 (p <0.05) and a value of t = -2.086. The significant and negative effects of the diversification strategy also apply to each bank performance variable based on LDR (influence magnitude of 5.9% and significance of 0.010), ROA (influence size of 3.6% and significance of 0.047), NPL (magnitude of influence of 3.6%. and a significance of 0.046), and CAR (magnitude of influence 3.9% and significance 0.038). It can be concluded that the higher the diversification, the lower the bank's performance.